The use of peripherally inserted central catheter lines with children in hospitals in the city of São Paulo - Vendramim, Patrícia (2008)
Descriptive and correlation study aimed at assessing the use of Peripherally Inserted Central Catheter (PICC) lines in pediatric patients, in hospitals of São Paulo, Brazil. The sample comprised 410 nurses from 29 hospitals; 57.9% of whom worked in private institutions, 61.6% in pediatric wards, and 38.4% in neonatal wards. PICC lines were inserted by 19.9% of the nurses, and the main training method was the certification awarded by medical specialties societies (47.0%). According to 52.0% of the sample participants, PICC lines are broadly used, yet nurses working for private institutions (p = 0.004) and in neonatology wards (p < 0.001) make a significantly higher use of them.